HUBUNGAN PEMANFAATAN PERPUSTAKAAN OLEH SISWA DENGAN HASIL BELAJAR PROGRAM KEAHLIAN TEKNIK BANGUNAN DI SMKN 1 PADANG - 609-616 , Fito Pratama (Universitas Negeri Padang, 2015)
Abstract This study was motivated by the low student learning outcomes Building Engineering Department at SMKN 1 Padang, the low student learning outcomes because of lack of use of the library by students Building Engineering Department which functions as a learning resource library, the purpose of this study was to determine the level of use of the library by students SMKN 1 Padang in Building Engineering Department as well as the use of libraries to disclose the relationship to the learning outcomes of students in SMKN 1 Padang Department of Buildings. This research is adescriptive studywith aquantitative approach. Population isclass XI1PadangSMKNacademic year2014/2105, amounting to 98people,samples were takenusingrandom samplingtechniques, whilethe sampling techniqueusingTaroYamaneformulaas much as 49people. In this studydatawas taken, there are two kinds, namelydata on theuse of the libraryas a variableXandlearning result (grades)as a variable Y.The results ofthe studythere was no associationwith theuse of the libraryanatarastudent learning outcomes(grades). It is suggested tolibrary managersto improvefurtherthe performance ofthe libraryso thatstudentshave the willtolibrarySMKN 1Padang. Keywords: the relationship, UtilizationLibrary, Learning Result